P-94 Enhanced supportive care in experimental cancer medicine trials at the christie nhs foundation trust. (1st March 2017) - Lilley, Shameem; Talbot, Hannah; Dean, Emma; Krebbs, Matthew; Cook, Natalie; Berman, Richard
Abstract : Background: Enhanced Supportive care (ESC) is a fresh approach to supporting people through cancer treatment. As its heart is better access to expertise in managing the adverse effects of cancer treatments. ESC is recognised nationally by NHS England, and received a Quality in Care (QiC) award (February 2016). We Previously piloted ESC in several disease groups. The work Demonstrated that timely supportive care improves patient experience and reduces hospital admissions. Incorporation of ESC within experimental cancer medicine is new in the UK. The aim is to help maximise patient recruitment and retention and enhance the patient experience within the context of experimental cancer medicine clinical trials (Phase I and non-randomised Phase II clinical trials). Methods: A Joint clinic was set up between the Experimental Cancer Medicine Team (ECMT) and the Supportive Care Team (SCT). These clinics are staffed by consultants from each team, research nurses and fellows and a clinical nurse specialist in supportive care. Patients being considered for or currently participating in a clinical trial are offered early referral to the supportive care team for assessment and management. Results: The pilot project began in September 2015. To date the SCT have undertaken 132 patient consultations within the ECMT. The predominant referral has been for optimisation of pain control, which is managed with specific consideration of the restrictions in the concomitant medication prescribing within Phase I trials. Conclusion: The ECMT at The Christie is the first early phase clinical trials unit to adopt ESC into practice. The ESC approach is now a routine part of the ECMT assessments of trial patients. Next steps will be to measure the impact of ESC on patient experience, eligibility for clinical trials, and admission avoidance.